Occurrence, risk assessment, and source of heavy metals in Liaohe River Protected Area from the watershed of Bohai Sea, China. (August 2021) - Li, Haixia; Xu, Li; Feng, Nana; Lu, Anxiang; Chen, Wei; Wang, Yupeng
Abstract: The occurrence, ecological risk, and source of heavy metals in the Liaohe River Protected Area from the watershed of the Bohai Sea were investigated. The maximum concentrations of Cu, Zn, Ni, Cd, Cr, Pb, and As in water were 8.50, 25.22, 3.80, 0.14, 1.76, 8.52, and 3.19 μg/L, respectively. The maximum concentrations of Cu, Zn, Ni, Cd, Cr, Pb, and As in sediment were 27.0, 109, 33.2, 0.56, 318, 43.7, and 29.3 mg/kg, respectively. The percentages of soil samples with observed concentrations above background values were 31.25%, 31.25%, 25%, 28.13%, 56.25%, 34.38%, and 37.5% for Cu, Cr, Zn, Ni, Cd, Pb, and As, respectively. Igeo suggested that sediments were polluted with Cd, Pb, As, Cr, and Zn, whereas soils were contaminated with all seven metals. Potential ecological risk index values exhibited that sites L25 and L12 were classified as moderately polluted in sediment and soil, respectively. Highlights: The pollution status of heavy metals in water from study area was safe. The pollution status of metals in water and sediment decreased in the last few years. Igeo suggested that Cr had the highest levels of accumulation in soil and sediment. Cadmium is the main element that causes potential ecological risk in soil and sediment.